Effect of process variables on the production of biomass-based activated carbons for carbon dioxide capture and sequestration - Rashidi, N.A. (Italian Association of Chemical Engineering - AIDIC, 2015)
The mitigation of carbon dioxide (CO2) from power plant generation using low-cost materials is a feasible technique to alleviate the global warming problems. In this present paper, CO2 adsorptions at atmospheric pressure and temperature were investigated using the biomass-based activated carbons produced from various sources that include palm shell, palm mesocarp fibre, coconut shell, coconut fibre, as well as rice husk. The preparation variables which include nature of precursors, particle size, heating rate, flow rate of activation agent, activation temperature, and residence times were evaluated. The Taguchi L25 orthogonal arrays through analysis of variance (ANOVA) statistical approach with 95 confidence limit had been used to study the effect of each operating variables at five levels each. Data analysis proved that both activation temperatures and types of starting materials were significant in producing activated carbons intended for CO2 capture, since p-value was < 0.05. The operating variables i.e. particle sizes, heating rate, flow rate, and residence time were found to be insignificant. Although the maximum CO2 adsorption capacity achieved by synthesised activated carbons were slightly lesser than the commercial activated carbon (1.79 mmol/g vs. 1.84 mmol/g), the proposed single-stage physical activation method in this study is an environmental-friendly approach to convert the massive agricultural wastes to value-added products, along with combating greenhouse problems caused by an uncontrolled release of greenhouse gases especially from electricity generation sectors. Copyright Â© 2015, AIDIC Servizi S.r.l.,.